2023
DOI: 10.1002/aoc.7000
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of gold nanoparticles using Heliotropium eichwaldi L and neuroprotective potential via anticholinesterase inhibition in rat brain

Abstract: Funding information Higher Education Commission of PakistanNanoparticles (NPs) are the fundamental backbone of nanotechnology due to their wide biomedical applications. Biogenic synthesis of gold NPs (AuNPs) using plant extracts are beneficial due to their nontoxicity, eco-friendliness, and simplicity. In this study, the HE-AuNPs were synthesized using Heliotropium eichwaldi L (HE) extract and then characterized by UV-visible (UV-vis) spectroscopy, Fourier transform-infrared (FT-IR), scanning electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…The presence of AgNPs is confirmed by the SPR bands in the 400 to 460 nm range 89 . These results are also supported by earlier literature 90 …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The presence of AgNPs is confirmed by the SPR bands in the 400 to 460 nm range 89 . These results are also supported by earlier literature 90 …”
Section: Discussionsupporting
confidence: 93%
“…89 These results are also supported by earlier literature. 90 According to scientific studies, FTIR is the best method for predicting functional groups. In this study, numerous vibrational stretches were observed at varied peaks that are related to phenolic, alcoholic, aromatic, carbonyl compounds of the protein, alkynes, conjugated aldehydes, ester, ether, carboxylic acid, aliphatic amines and halo compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The significant AChE inhibition by BNPs as related to other tested inhibitors is due to their size, surface area, and shape, and AD is best treated by combining a mixture of two different metals due to their collaborative effect. Sher and Ahmed et al, Wang et al, and Sher and Alkhalifa et al [90][91][92] reported that NPs exhibited anti-AChE activity by adsorption or interaction with the enzyme. According to Sher and Ahmed et al and Rajakumar et al, 89,93 because of the NPs' lipophilicity and enzyme molecules' hydrophobicity, the NPs exhibited attraction to the AChE enzyme.…”
Section: Discussionmentioning
confidence: 99%
“…According to Ref. [53], Ag NPs have binding affinity to the AChE enzyme because of their lipophilicity and the hydrophobicity of the environment of the AChE molecules. The results of the present study are also in good accordance with a previous report [54].…”
Section: Discussionmentioning
confidence: 99%